Sarcopenia in Indonesian Community-Dwelling Elderly: The Prevalence and Influencing Factors within the Primary Care Setting - Rahayu, Sri Ratna; Putriningtyas, Natalia Desy; Candra, Adiska Rani Ditya; Azizan, Azliyana; Azmi, Alia; Mohamad Shaifuddin, Siti Norashikin; Merzistya, Aufiena Nur Ayu; Affandi, Mustafa Daru; Muflikhah, Zuyyinatun; Pranindita, Salsabila Kinaya (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
Determining the prevalence of sarcopenia and identifying associated factors can aid in early detection and treatment among community-dwelling elderly. This study aims to estimate the prevalence of sarcopenia and identify associated factors. This cross-sectional study was conducted in the elderly community within the two areas of Public Health Center, Semarang, Indonesia, through random sampling. Sarcopenia was defined based on the 2019 Asian Working Group for Sarcopenia (AWGS) criteria. Data on socio-demographics, clinical, and functional status were collected and associated factors analyzed using multivariable logistic regression. Of the 153 participants, the prevalence of severe sarcopenia was 50.33%, and overall sarcopenia prevalence was 44.44%. Elderly individuals with severe sarcopenia had a mean age of 69.45, with a higher occurrence in women (79.2%) compared to men. Age (p=0.003; APR: 1.105; 95% CI: 1.035-1.180), toilet type (p=0.002; APR: 4.194; 95% CI: 1.677-10.493), and being female (p=0.049; APR: 2.341; 95% CI: 1.003-5.460) were identified as risk factors for severe sarcopenia. The prevalence of severe sarcopenia is elevated among community-dwelling elderly. Sarcopenia was defined as low muscle mass with low handgrip strength and/or low gait speed. Routine check-ups are needed to detect sarcopenia and its risk factors in primary health care to enable early intervention for sarcopenia in the elderly.